Upregulation of IRF9 Contributes to Pulmonary Artery Smooth Muscle Cell Proliferation During Pulmonary Arterial Hypertension - Chen, Yong-Jie; Li, Yi; Guo, Xian; Huo, Bo; Chen, Yue; He, Yi; Xiao, Rui; Zhu, Xue-Hai; Jiang, Ding-Sheng; Wei, Xiang (Frontiers in Pharmacology, 2021)
Abnormal proliferation of pulmonary artery smooth muscle cells (PASMCs) is a critical pathological feature in the pathogenesis of pulmonary arterial hypertension (PAH), but the regulatory mechanisms remain largely unknown. Herein, we demonstrated that interferon regulatory factor 9 (IRF9) accelerated PASMCs proliferation by regulating Prohibitin 1 (PHB1) expression and the AKT-GSK3β signaling pathway. Compared with control groups, the rats treated with chronic hypoxia (CH), monocrotaline (MCT) or sugen5416 combined with chronic hypoxia (SuHx), and mice challenged with CH had significantly thickened pulmonary arterioles and hyperproliferative PASMCs. More importantly, the protein level of IRF9 was found to be elevated in the thickened medial wall of the pulmonary arterioles in all of these PAH models. Notably, overexpression of IRF9 significantly promoted the proliferation of rat and human PASMCs, as evidenced by increased cell counts, EdU-positive cells and upregulated biomarkers of cell proliferation. In contrast, knockdown of IRF9 suppressed the proliferation of rat and human PASMCs. Mechanistically, IRF9 directly restrained PHB1 expression and interacted with AKT to inhibit the phosphorylation of AKT at thr308 site, which finally led to mitochondrial dysfunction and PASMC proliferation. Unsurprisingly, MK2206, a specific inhibitor of AKT, partially reversed the PASMC proliferation inhibited by IRF9 knockdown. Thus, our results suggested that elevation of IRF9 facilitates PASMC proliferation by regulating PHB1 expression and AKT signaling pathway to affect mitochondrial function during the development of PAH, which indicated that targeting IRF9 may serve as a novel strategy to delay the pathological progression of PAH.